Critique of modern rationality in the work of Franz Hinkelammert - RAMAGLIA, Dante (Utopía y Praxis Latinoamericana, 2022)
The central theme of Franz Hinkelammert's work is the critique of modernity. In this sense, the different registers in which this criticism unfolds are reviewed. A fundamental thesis denounces the forms of exploitation and destruction to which the civilizational crisis associated with the development of capitalism has led. Hence, the forms of rationality to which modern culture has given rise are reviewed, together with the determinations that subjectivity experiences from this historical period. Likewise, the surpassing alternatives that are proposed in the author's theoretical elaborations are shown.